Effect of soil depth and seasonal change on spore population and mycorrhizal colonization of kinnow and rough lemon seedlings - and M.S. KANG, RAMA S. SINGH, HARDIP SINGH (Indian Phytopathology, 2002)
Variation in spore density and VA mycorrhizal r09t colonization of kinnow and rough lemon seedlings were correlated with change of season. The infection of VA mycorrhizal fungi was observed maximum in June and minimum in November. The maximum and minimum spore population of endophytes in soil were recorded in June and October respectively. VA mycorrhizal colonization and spore density also decline beyond 30 ern soil depth. The mycorrhizal inoculation in soil significantly increased the root, shoot length and number of leaves per rough lemon seedlings.